Increasing uptake of colorectal cancer screening in Korea: a population-based study - Oh Jae; Hahm Myung-Il; Lee Hoo-Yeon; Jun Jae; Choi Kui; Park Eun-Cheol (BMC, 2010)
Abstract Background Colorectal cancer (CRC) screening rates are low in most Asian countries and remain largely unknown. This study examined trends in CRC screening rates after the introduction of the Korean National Cancer Screening Programme (NCSP) and determined the factors associated with uptake of CRC screening by test modality over time. Methods An annual population-based survey conducted through nationally representative random sampling from 2005-2008. In total, 3,699 participants from the 2005-2008 surveys were selected as study subjects. Face-to-face interviews were performed to assess the utilization rate of CRC screening by each screening modality. Results Overall, CRC screening within the recommended time interval increased significantly from 22.9% in 2005 to 36.6% in 2008 (p < 0.001). The proportion of subjects receiving a fecal occult blood test (FOBT) test within the previous year increased significantly from 7.2% in 2005 to 21.3% in 2008 (p < 0.001). Increases in FOBT testing were highest among those who had a lower income status (relative difference = 511.9%) and women (relative difference = 266.1%). Endoscopy use also increased from 18.0% in 2005 to 20.5% in 2008, albeit not significant. Overall, those who were male, non-smokers, 60-69 years old, and had a higher income status were more likely to have undergone up-to-date endoscopy and CRC screening. Conclusions This study revealed a substantial increase in up-to-date CRC screening in the general population from 2005 to 2008. However, more than half of adults in Korea are still not up-to-date with their CRC tests. It will be important to continue to investigate factors associated with up-to-date CRC screening by each modality.